Logaritmo e a régua de cálculo: uma proposta de ensino - Pedrosa, Rose Elizângela Martins (2018)
This work presents a brief historical account of the appearance of logarithms, highlighting the names of John Napier, who developed the first ideas on the subject, and Henrry Briggs, who perfected this idea. The work includes an overview of the existent dissertations in the PROFMAT about the subject, highlighting some relevant aspects frequent in these works. This work also brings an analysis of the content of logarithms in seven textbooks used by students of Basic Education. Finally, the dissertation contains a didactic sequence and the report of its implementation. The sequence is a teaching plan that uses the slide rule to develop the study of logarithms under the perspective of the History of Mathematics. This proposal is based on the booklet entitled “Logarithms and the Slide Rule: a teaching proposal”.